Transactions on Intelligent Welding Manufacturing Volume I No. 3 2017 (Transactions on Intelligent Welding Manufacturing,, 2018)
Transactions on Intelligent Welding Manufacturing (TIWM) mainly publishes selected high quality papers from the proceedings of the conference series "International Workshop on Intelligentized Welding Manufacturing (IWIWM)" and "International Conference on Robotic Welding, Intelligence and Automation (RWIA)", as well as freely contributed and peer-reviewed original research papers.